The Role of Digital Leadership in Transformation and Employee Creativity: A Case Study at PT. Ong Convection Pamekasan - Wahyuni, Ummy; Fathorrahman, Fathorrahman; Zainurrafiqi, Zainurrafiqi (Al-Amien Prenduan for Islamic Institute, 2025)
This study aims to examine the influence of Digital Leadership on employee performance at PT. Ong Konveksi Pamekasan, by considering the mediating role of Digital Transformation and Employee Creativity. The sample used in this study involved 90 employees of PT. Ong Konveksi Pamekasan. A quantitative approach was applied with a data collection method using a questionnaire, and the analysis tool used was WarpPLS. The results of the study indicate that Digital Leadership has a significant effect on Digital Transformation, Employee Creativity, and Employee Performance. Digital Transformation and Employee Creativity are also proven to improve Employee Performance. This study contributes to the literature on the role of Digital Leadership in improving employee performance through digital transformation and creativity, as well as providing practical insights for companies in implementing effective digital leadership strategies